An investigation of a two-stage nonlinear vibration isolation system - Lu, Zeqi; Brennan, Michael J. [UNESP]; Yang, Tiejun; Li, Xinhui; Liu, Zhigang (Elsevier, 2013)
This paper investigates the most desirable configuration of a two-stage nonlinear vibration isolation system, in which the isolators contain hardening geometric stiffness nonlinearity and linear viscous damping. The force transmissibility of the system is used as the measure of the effectiveness of the isolation system. The hardening nonlinearity is achieved by placing horizontal springs onto the suspended and intermediate masses, which are supported by vertical springs. It is found that nonlinearity in the upper stage has very little effect and thus serves little purpose. The nonlinearity in the lower stage, however, has a profound effect, and can significantly improve the effectiveness of the isolation system. Further, it is found that it is desirable to have high damping in the upper stage and very low damping in the lower stage. © 2012 Elsevier Ltd.
Keywords: Geometric stiffness; High damping; Isolation systems; Linear viscous; Nonlinear vibration isolation system; Upper stages; Hardening; Damping